Comparison of female breast cancer between Russia and Germany: a population-based study on time trends and stage at diagnosis - Mahanani, Melani Ratih; Valkov, Mikhail; Agaeva, Anna; Kaucher, Simone; Pikalova, Lidia V.; Grishchenko, Maksim Y.; Zhuikova, Lilia D.; Jaehn, Philipp; Winkler, Volker (Cancer epidemiology, 2022)
Objectives - While a mammography-screening program (MSP) is being offered systematically in Germany since 2009, the dispanserizatsiya has been implemented in Russia since 2013. This study examined trends of stage at breast cancer diagnosis in two Russian regions and compared the results with the development in Germany. In addition, we aimed to gain further insights into the early detection of breast cancer in Russia. - Methods - Incidence data from two cancer registries in Russia and 12 population-based cancer registries in Germany were used to analyse breast cancer incidence rates among women above age 30 over time. Further, we calculated rate ratios to compare the age group-specific incidence rates after the implementation of MSP in Germany (2010-2014) with the period before implementation (2003-2005) separately for each tumour stage and all stages combined. - Results - During the study period from 2003 to 2014, age-standardised rates for breast cancer were 54.6 and 116.7 per 100,000 for Russia and Germany, respectively. The proportion of the T1 stage at diagnosis among Russian women aged 50 + is half than that in Germany. Nevertheless, we observed an increasing trend of early-stage alongside the reduction of advanced-stage incidence rates of breast cancer in Russia. - Conclusions - The observed trend in Russia may reflect overall positive changes in early detection of breast cancer, with actual proportion of T1 stage still far behind Germany. Advances in breast cancer screening efforts through the dispanserizatsiya may help to further reduce the breast cancer burden.